PECULIARITIES OF ANTI-CRISIS MANAGEMENT OF THE ENTERPRISE - Fedyk , О. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
The political and economic crisis in Ukraine, which is caused by the military invasion of the troops of the Russian Federation to Ukraine, raised attention to creation of effective mechanisms for implementation of anti-crisis management of the enterprise in order to ensure stability of its operation and support its competitiveness. Uncertainty of the external and internal environment, presence of significant risks of economic activity, lack of knowledge in the field of legal protection regarding occurrence of force majeure circumstances, untimely responses to crisis manifestations can lead to stagnation of the enterprise operation and its bankruptcy. It is worth noting that anti-crisis management is based not only on general patterns inherent in management processes, but also on specific features related to implementation of anti-crisis procedures. In the majority of scientific sources, anti-crisis management is considered as reactive and preventive one. Despite distinguishing the mechanisms of anti-crisis management, it is worth highlighting a purposeful type of preventive and reactive (enhanced) leadership. The main goal of reactive management is to get the company out of the crisis situation. Under such conditions, actions of the management apparatus are directed to localize the consequences of the crisis phenomena and to determine mechanisms and methods of overcoming the crisis. These mechanisms are primarily aimed at ensuring financial control and auditing of business processes, the main goal of which is to bring the enterprise out of the crisis conditions. Mechanisms and methods of preventive management represent a management complex, which, unlike traditional anti-crisis management, contains management actions aimed at ensuring the enterprise’s effective performance, monitoring and preventing occurrence of crisis phenomena, control over deviations of the actual values of the specified parameters from target benchmarks.